2012
DOI: 10.1038/nature11628
|View full text |Cite
|
Sign up to set email alerts
|

Autism-related deficits via dysregulated eIF4E-dependent translational control

Abstract: Hyperconnectivity of neuronal circuits due to increased synaptic protein synthesis is postulated to cause Autism Spectrum Disorders (ASD). The mammalian target of rapamycin (mTOR) is strongly implicated in ASD via upstream signaling. However, downstream regulatory mechanisms are ill-defined. We show that knockout (KO) of the eukaryotic translation Initiation Factor 4E-Binding Protein 2 (4E-BP2), an eIF4E-repressor downstream of mTOR, or eIF4E overexpression lead to increased translation of neuroligins, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
506
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 455 publications
(549 citation statements)
references
References 46 publications
(63 reference statements)
22
506
0
3
Order By: Relevance
“…By contrast, NLGN2 tends to locate preferentially to inhibitory synapses via an interaction with gephyrin [46]. A recent paper by Gkogkas et al [47] provides a promising link between NLGN and the mGluR theory. The authors investigated a model of excessive protein synthesis by eukaryotic translation initiation factor 4E (eIF4E) overexpression or depression (knockout of eIF4E-binding protein 2) and found that it resulted in over-translation of NLGN, increased excitatory-to-inhibitory transmission ratio and autism-like behavioural symptoms.…”
Section: The Synaptic Theory Of Autismmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, NLGN2 tends to locate preferentially to inhibitory synapses via an interaction with gephyrin [46]. A recent paper by Gkogkas et al [47] provides a promising link between NLGN and the mGluR theory. The authors investigated a model of excessive protein synthesis by eukaryotic translation initiation factor 4E (eIF4E) overexpression or depression (knockout of eIF4E-binding protein 2) and found that it resulted in over-translation of NLGN, increased excitatory-to-inhibitory transmission ratio and autism-like behavioural symptoms.…”
Section: The Synaptic Theory Of Autismmentioning
confidence: 99%
“…B 369: 20130143 is enhanced, the excitatory/inhibitory (E/I) ratio is increased. Reduction of NLGN1 levels using siRNA restored E/I balance and reversed deficits in social interaction behaviour [47]. Another example is the case of the Shank2 KO; it was shown that acute administration of either the NMDAR partial agonist D-cycloserine or an mGluR5-positive allosteric modulator (3-cyano-N-(1,3-diphenyl-1H-pyrazol-5-yl) benzamide) could rescue the electrophysiological and social impairments in the KO mice [67].…”
Section: Rescuing Autism Phenotypementioning
confidence: 99%
“…Answering these questions is difficult because the disorder is multifactorial in nature with multiple genetic variants and environmental factors contributing to the core symptoms (10)(11)(12)(13). To face this challenge, extensive efforts have been made to identify the targeting and functional convergence of the autism-risk genes, such as those involved in translation regulation (14)(15)(16) and long-range connectivity among different brain regions (17)(18)(19). These targets and functions provide a better biological basis for elucidating the causal paths between risk genes and the disorders of autism.…”
mentioning
confidence: 99%
“…Altered regulation of translation initiation has been linked to prion formation (9) and to several human diseases, including autism (10) and cancer (11). eIF4E is overexpressed in a variety of tumor cells (12,13).…”
mentioning
confidence: 99%